2023
DOI: 10.1186/s12902-023-01366-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between lipid metabolism and periodontitis in obese patients: a cross-sectional study

Abstract: Background To investigate the association between clinical periodontal parameters of periodontitis, serum lipid metabolism markers and adipokines’ levels in patients with obesity and periodontitis. Methods A total of 112 patients admitted to Hospital of Xi’an Jiaotong University were included in this study. They were divided into normal body weight group (18.5 < body mass index, BMI < 25, n = 36), overweight group (25 ≤ BMI < 30, n = 38), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…No significant difference in circulating RBP4 level was observed among participants with and without periodontitis [19,23,26] (Figure 2, SMD = 1.38; 95% CI: −0.18-2.94, p = 0.08). In addition, a significant difference in serum visfatin level was found between two groups of periodontitis participants with and without obesity, with a higher level of serum visfatin found in OP group (Figure 3, MD = 4.21; 95% CI: 2.65-5.77, p < 0.00001) [28,33].…”
Section: Subgroup Meta-analysismentioning
confidence: 87%
See 4 more Smart Citations
“…No significant difference in circulating RBP4 level was observed among participants with and without periodontitis [19,23,26] (Figure 2, SMD = 1.38; 95% CI: −0.18-2.94, p = 0.08). In addition, a significant difference in serum visfatin level was found between two groups of periodontitis participants with and without obesity, with a higher level of serum visfatin found in OP group (Figure 3, MD = 4.21; 95% CI: 2.65-5.77, p < 0.00001) [28,33].…”
Section: Subgroup Meta-analysismentioning
confidence: 87%
“…The random effect model was selected and, in the included two studies, no significant difference in serum RBP4 level [23,26] was found between the groups of obese participants with periodontitis and systematic healthy participants without periodontal diseases (NnP) (Figure 4, SMD = 6.76; 95% CI: −5.34-18.87, p = 0.27). Furthermore, a significant difference was found in serum visfatin level between the groups of obese participants with periodontitis and systematic healthy participants without periodontal diseases A higher level of serum visfatin was found in the OP group than NnP (Figure 5, MD = 13.02; 95% CI: 7.34-18.70, p < 0.00001) [28,30,33]. The quality assessment of the included five observational studies using the Newcastle-Ottawa Scale and Cochrane-advocated ROBINS-I tools for two interventional articles are shown in Tables S2 and S3.…”
Section: Subgroup Meta-analysismentioning
confidence: 88%
See 3 more Smart Citations